ASSESSMENT OF TWO PHASE FLOW IN A VENTURE CONVERGENT- DIVERGENT NOZZLE. - Fayadh M. Al-Dulaimy (Tikrit Journal of Engineering Sciences, 2015)
The present study emphasized on the information of cavitations during the dual phase flow i.e. (water and vapor) in venture  converge-diverge nozzle. The choice of nozzle with a transparent material (PMMA), was found suitable for the observation and measurements. The model of this problem of defining dual compressible viscous flow, and k-epsilon model. The comparisons of numerical calculation and experimental observation were found to be comparatively coincidable in cavitational zone and throat pressure, and fractional phase flow.